Rawls, Ideal Theory and the Relevance of Context - Barbosa, Evandro; Alves Costa, Thaís (Sofia, 2026)
The article investigates how John Rawls’s theory of justice both accommodates and limits the relevance of context within his account of justice as fairness, drawing on the distinction between ideal and non-ideal theory. First, we reconstruct the ideal dimension of the Rawlsian framework, with emphasis on the circumstances of justice, the moral psychology of agents, and the notion of the quasi-stability of a well-ordered society. We then offer an account of these non-ideal circumstances as a kind of challenging context that serves as a test for the scope of ideal theories of justice. Engaging with the debate on contextualism in justice, and in particular with so-called iterative contextualism, the article defends a more open reading of Rawls’s theory, one that can enter into dialogue with this kind of approach without abandoning the normative core of his proposal as presented in the ideal part of his theory.
Keywords: ideal theory; non-ideal theory; context; justice